Organoids for Obesity-related Diseases: Disease Models and Drug Screening - Xie, Jiaman; Zhou, Keyi; Zhang, Hanyu; Jiang, Zhijia; Fang, Jingxian (Current Stem Cell Research & Therapy, 2025)
BackgroundOrganoids are three-dimensional structures that faithfully mimic the intricate internal environment of the human body. Compared to conventional models, they demonstrated superior performance. Recently, they have emerged as valuable platforms for modeling obesity-related diseases and advancing therapeutic strategies.ObjectivesThis review not only aimed to simply discuss the limitations of 2D cellular and animal models for obesity-related diseases but also highlighted the importance of developing organoids to better understand the relationship between obesity, lipid metabolism, glucose homeostasis, and chronic inflammation. It also identifies the challenges and potential directions for organoid applications in these diseases.MethodsWe searched for keywords related to organoids, obesity, lipid metabolism, glucose homeostasis, chronic inflammation, disease models, and drug screening in scientific research databases.ResultsOrganoids have emerged as promising tools for investigating the pathophysiology of diseases and developing therapeutic interventions. They have effectively bridged the gap in research on obesity-related diseases between conventional experimental models and the human body. They could offer more efficient and physiologically relevant experimental models while also improving the treatment efficacy for individuals with obesity-related conditions.ConclusionOrganoids are beneficial for investigating obesity-related diseases. However, it is imperative to implement standardised culture procedures to improve reproducibility and broaden their application. Combining medicine and science to create these processes and minimise variation can increase the reliability and consistency of organoid cultures and provide new opportunities for addressing obesity-related diseases.
Keywords: obesity